Älgens roll i ett neolitiskt tänkande. Om fångstgropar, skärvstensvallar och hällbilder i mellersta Norrland - Ylva Sjöstrand (Primitive Tider, 2021)
The moose and its place in the Neolithic thinking The study argues that the concept of Neolithisation can be applied to the Stone Age hunter-gatherer communities of Middle Norrland. The point of departure is that Neolithisation can be regarded as a form of production, a cognitive structure, rather than being reduced to a term signifying the presence of farming or animal husbandry. Since phenomena such as collective practices and organisational endeavours comprised the prerequisites for the stationary archaeological remains in Middle Norrland, the notion that this society has been permeated by what I refer to as a ”Neolithic way of thinking” is well supported.